The concept of John Locke's liberalism - Podkovenko, Tetiana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The article considers the political and legal aspects of the teachings of the famous English thinker John Locke, which substantiate the formation of the state and law. The main postulates of his teachings are presented in numerous pamphlets, treatises and essays, among which the central place is occupied by his work "Two Treatises on Government" (1690). In it, J. Locke set out his views on the origin, purpose and organization of state power and its limits. The author consistently reveals the processes of humanity's transition from the natural state and natural freedom to a state-organized society and guaranteed freedom. Being the founder of liberalism, substantiating the concept of social contract and the right of the people to counteract the arbitrariness of power, the thinker identified the characteristics of the liberal state and the peculiarities of its interaction with civil society. It is no coincidence that John Locke was recognized as the founding father of the European Enlightenment of the XVIII century.The concept of separation of powers and the related system of containments and counterweights are analyzed. The theory of social contract allows us to look at the nature of power, as well as the factors that limit state power. The essence of Locke's position is that natural freedom is preserved within the social state, but is reasonably limited by the power of the community, based on law and order.The thinker identified several reasons for popular opposition to the legislature and the executive branch: first, the abuse of the legislature, which threatens the lives and property of individuals, then, loss of self-confidence in the executive branch, for example, when it tries to circumvent the legislature by turning its will into law or hinders the legislature from meeting, or changes the terms of the election. Such abuses destroy the system of good governance created by the people and threaten the disintegration of society.The main task of political society, according to Locke, is to preserve the fundamental human right to property, which in his view includes the right to life, liberty and property. Accordingly, J. Locke defines the triad of inalienable rights - the right to life, the right to liberty and the right to property. This is the basis of self-realization of a person in a civil state and at the same time it is the basis of the political community.In his socio-political views, Locke proceeded from the basic tenets of the concept of natural law. It is substantiated that the humanistic content of the political and legal doctrine of J. Locke is most fully expressed in the concept of human rights. J. Locke's liberal ideas on understanding human freedom and its relationship with the freedom of others in a politically organized society are highlighted.